2016
DOI: 10.1088/1748-9326/11/11/114010
|View full text |Cite
|
Sign up to set email alerts
|

The role of capital costs in decarbonizing the electricity sector

Abstract: Low-carbon electricity generation, i.e. renewable energy, nuclear power and carbon capture and storage, is more capital intensive than electricity generation through carbon emitting fossil fuel power stations. High capital costs, expressed as high weighted average cost of capital (WACC), thus tend to encourage the use of fossil fuels. To achieve the same degree of decarbonization, countries with high capital costs therefore need to impose a higher price on carbon emissions than countries with low capital costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(85 citation statements)
references
References 33 publications
1
79
0
1
Order By: Relevance
“…The feasibility of a transition away from unabated coal will also depend on available technological alternatives and accompanying policy instruments. For example, policies that de-risk investments into lowcarbon technology can significantly lower the carbon price level necessary to induce a coal phase-out [44]. In addition, increased deployment of low-carbon energy sources will require improved grid integration to be able to deal with the variable availability of solar and wind power appropriately [32].…”
Section: The Political Economy Of Phasing Out Coalmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of a transition away from unabated coal will also depend on available technological alternatives and accompanying policy instruments. For example, policies that de-risk investments into lowcarbon technology can significantly lower the carbon price level necessary to induce a coal phase-out [44]. In addition, increased deployment of low-carbon energy sources will require improved grid integration to be able to deal with the variable availability of solar and wind power appropriately [32].…”
Section: The Political Economy Of Phasing Out Coalmentioning
confidence: 99%
“…Countries refraining from coal use or extraction should be compensated accordingly. Otherwise, poor countries are unlikely to bear the additional costs of clean energy sources [45], especially with regard to the required high initial investment costs in the face of capital constraints [44]. Such support could take the form of e.g.…”
Section: The Political Economy Of Phasing Out Coalmentioning
confidence: 99%
“…This is because society as a whole can effectively reduce the non-systematic risk that individual investors bear to zero by pooling risks across the entire population [45,46]. Lower discount rates lead to lower LCOE, with this effect being more pronounced for capital-intensive technologies, especially nuclear power plants, compared to plants with higher operational costs, such as natural gas [47].…”
Section: Sum Of Plant-level Costs In the Form Of Levelized Cost Of Elmentioning
confidence: 99%
“…However, Brückmann [34] found that no tightening of this WACC gap has occurred in recent years. An interaction between the WACC and the price for CO 2 emissions has been found by Hirth and Steckel [35]. Accordingly, higher WACC require higher CO 2 prices to achieve the same reduction target.…”
Section: Introductionmentioning
confidence: 84%